Manual de funciones para la dirección de talento humano del Gobierno Autónomo Descentralizado Municipal del cantón Urdaneta, año 2011 - Muñoz Meza, Martha Jessenia (2012)
The investigation gathers information about employees functions for the direction of Human Talent of Gobierno Autónomo Descentralizado Municipal del cantón Urdaneta, in short has as general aim provide a document that describes and includes the activities that must fulfill each of the employees on the basis of the functions them assigned. The summary of the information was realized by means of the Autónomo Descentralizado Municipal del cantón Urdaneta application of the technologies of investigation since they are the survey applied to the workers and employees of the clerical staff of the, with end of knowing the activities that every employee recovers. Whereas the interview was applied to the Authorities and the Directors of the Units the directly related to the movements of the personnel. The analysis of the results will allow to know the degree of fulfillment of the workers and employees to the assigned functions. In addition it will allow to determine if the assignment of the assigned functions they have been on the basis of the academic preparation and professional profile that every employee possesses. Before the exposed thing the production proposes itself of the manual one of functions for the Unit of Human Talent of the Autónomo Descentralizado Municipal del cantón Urdaneta, as alternative that determines the specific functions that every employee must fulfill, the same ones that will have to be assigned in agreement to the academic preparation and to the professional profile that each of them possess. With which one tries to fulfill the tasks assigned with efficiency, efficiency and efficiency, and hereby to optimize and to reveal the services that there gives the Autónomo Descentralizado Municipal del cantón Urdaneta.